2016
DOI: 10.1589/jpts.28.1720
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of neural mobilization and infrared on the mechanics of the median nerve

Abstract: [Purpose] This study analyzed the acute effects of infrared and neural mobilization on the median nerve on the range of elbow extension of the dominant limb. [Subjects and Methods] Forty participants from university, neurologically asymptomatic, 12 males and 28 females (22.8 ± 1.9 years), were randomly divided into four groups: Group 1 (control) rested for 25 minutes in the supine position; Group 2 received the specific neural mobilization for the median nerve; Group 3 received an application of infrared for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Neural mobilization includes manual therapy techniques (Gliding and stretching). It is used to treat adverse neural tension and is considered to improve neurodynamics, axoplasmic flow, maintaining dynamic balance between neural tissues and surrounding mechanical interfaces and thus decreases the mechanosensitivity 28 . T. Hall et al also concluded that neurodynamic sliding interventions can be thought to decrease neural mechenosensitivity and this was supported by other studies too.…”
Section: Discussionmentioning
confidence: 99%
“…Neural mobilization includes manual therapy techniques (Gliding and stretching). It is used to treat adverse neural tension and is considered to improve neurodynamics, axoplasmic flow, maintaining dynamic balance between neural tissues and surrounding mechanical interfaces and thus decreases the mechanosensitivity 28 . T. Hall et al also concluded that neurodynamic sliding interventions can be thought to decrease neural mechenosensitivity and this was supported by other studies too.…”
Section: Discussionmentioning
confidence: 99%
“…Although NM is used to gain flexibility, 13 , 14 muscle strength, 15 reduce pain, 16 , 17 , 18 , 19 and accelerate tissue repair, 11 there are controversies regarding the efficacy of this technique in experimental studies in individuals with nerve compression; this might be due to the diversity of protocols used, with different intensities and positioning. 4 The present study also presented a different protocol, which sought to adapt, in an animal model, the positioning of median nerve stretching done in clinical practice with humans.…”
Section: Discussionmentioning
confidence: 99%
“…The participant was asked to turn their head to the opposite side and the stretching effect was increased while applying this technique. The mobilization was terminated by waiting 3 seconds at the last point, and the same process was repeated three times (Kim et al, 2016;Nunes et al, 2016). The neural mobilization technique was always applied by the same physiotherapist (NG) who trained in manual therapy.…”
Section: Median Nerve Mobilization Techniquementioning
confidence: 99%